Ovarian hyperstimulation syndrome. Issue 12 (December 2017) - Balakumar, Vidhya; Ramalingam, Mythili; Kay, Vanessa
Abstract: Ovarian hyperstimulation syndrome (OHSS) is a preventable, iatrogenic multi-organ disorder. It develops as a complication of assisted reproductive treatments and in most cases is self-limiting, although can occasionally be life threatening. It has been estimated that severe OHSS occurs in approximately 1% of treatments with recent HFEA reporting an increase in the incidence. The RCOG has recently updated the Green Top Guideline (GTG) on the prevention and management of OHSS and the new additions will be emphasised here.